Joanne Chory (1955–2024): Plant geneticist extraordinaire - Jennifer L. Nemhauser; Detlef Weigel (Proceedings of the National Academy of Sciences, 2025)
Joanne Chory (1955–2024) was a pioneering biologist whose research transformed our understanding of plant growth and development. Her groundbreaking work, based on many clever genetic screens, established a complete signaling pathway for brassinosteroids, from the biosynthesis of this important class of plant hormones and their transmembrane receptor to cytoplasmic and nuclear effectors. A beloved mentor and visionary leader, Chory championed science as both a rigorous discipline and a force for good. In her final years, she mobilized plant biologists across the world to address climate change, inspiring an entire generation to see plants as allies in securing a sustainable future. Her legacy lives on in her discoveries, her students, and the global scientific community she helped shape.